PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMUNIKASI ORGANISASI SEKOLAH TERHADAP KOMPETENSI GURU DAN DAMPAKNYA TERHADAP KUALITAS PEMBELAJARAN - Aan Hermansyah (Universitas Majalengka, 2020)
This study aims to determine: 1) The leadership of the school principal, organizational communication, teacher competencies, and the quality of learning. 2) The influence of the principal's leadership on the competence of teachers, 3) The effect of organizational communication on the competence of teachers, 4) The influence of school principlas leadership and organizational communication together on the competence, and 5) the effect of teacher competence on the quality of learning in state high schools in Majalengka Regency. This research method is a quantitative research method with descriptive and verification analysis techniques. Descriptive method using the calculation of frequency distribution, scoring and average value, while the verification method using path analysis. The sampling technique was taken by cluster proportional random sampling. Descriptive research results indicate that the principal's leadership, organizational communication, teacher competence and learning quality are in the good category. The results of the verification study prove that leadership and organizational communication have a positive and significant effect on teacher competency either partially or simultaneously. Teacher competence has a positive and significant effect on the quality of learning